The Moderating Effect of Mental Toughness: Perception of Risk and Belief in the Paranormal. Issue 1 (February 2019) - Drinkwater, Kenneth; Dagnall, Neil; Denovan, Andrew; Parker, Andrew
This research demonstrates that higher levels of mental toughness provide cognitive-perceptual processing advantages when evaluating risk. No previous research, however, has examined mental toughness in relation to perception of risk and paranormal belief (a variable associated with distorted perception of causality and elevated levels of perceived risk). Accordingly, the present paper investigated relationships between these factors. A sample of 174 participants completed self-report measures assessing mental toughness, general perception of risk, and paranormal belief. Responses were analyzed via correlations and moderation analyses. Results revealed that mental toughness correlated negatively with perception of risk and paranormal belief, whereas paranormal belief correlated positively with perception of risk. For the moderation effects, simple slopes analyses indicated that high levels of MT and subfactors of commitment and confidence reduced the strength of association between paranormal belief and perceived risk. Therefore, MT potentially acts as a protective factor among individuals who believe in the paranormal, reducing the tendency to perceive elevated levels of risk.